2013
DOI: 10.1049/iet-ipr.2013.0067
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive sampling approach for volumetric shadows in dynamic scenes

Abstract: Ray marching is an important technique to generate volumetric lighting effects. However, it is very expensive for each pixel on the screen, especially in dynamic scenes. The authors propose an adaptive approach to reduce samples for volumetric shadows in the time domain. In dynamic scenes, shadow volumes of moving objects are created and are rasterised to decide pixels that cannot be reused. The authors use a stencil buffer to maintain the information of screen pixels by recomputing or just using the previous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The volumetric light was the same as obtaining 2D medical images from 3D magnetic resonance(MRI) or computed tomography (CT) data. The primary previous studies on volumetric light were found in References [14][15][16][17][18][19]. Later improvement was proposed by volumetric shadow method, which can be combined with epipolar sampling for further acceleration.…”
Section: Plos Onementioning
confidence: 99%
“…The volumetric light was the same as obtaining 2D medical images from 3D magnetic resonance(MRI) or computed tomography (CT) data. The primary previous studies on volumetric light were found in References [14][15][16][17][18][19]. Later improvement was proposed by volumetric shadow method, which can be combined with epipolar sampling for further acceleration.…”
Section: Plos Onementioning
confidence: 99%
“…Lin H. et al, [ 21 ] proposed a method to reduce the number of sample points for generating volumetric shadows in dynamic scenes. This method based on decision whether a pixel should be re-computed or used the information from previous frame.…”
Section: Related Workmentioning
confidence: 99%
“…Ray marching method is most common than other proposed techniques that uses to generate light scattering. This method is computed light scattering by evaluating all points of the light source along view ray until up to the viewer Lin, et al [21]. Therefore, several of methods have adopted this concept by using a trick to reduce of sample points along view rays to evaluate all points that potential seen from light source.…”
Section: Introductionmentioning
confidence: 99%